Analisis Perencanaan Karier Pegawai pada PT XYZ - Ika Anggreiny; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The purpose of this research is to find out the process, obstacles, and solutions of career planning at PT XYZ. This research uses a qualitative method, namely by analyzing and interpreting the problems found in a narrative manner. The sampling technique used was purposive sampling. The data collection techniques used in this research consist of primary data and secondary data. Primary data was obtained by conducting observations, interviews, and documentation, while secondary data was obtained through books and previous research journals related to the research. The data analysis techniques used in this research are data collection, data reduction, data presentation, and verification and conclusion drawing. The results of this study indicate that PT XYZ has implemented career planning for employees through assessment and career development once a year. In addition, there are also obstacles that occur in employee career planning, namely the lack of seriousness of employees in participating in career planning activities on the grounds that time clashes with deadlines for employee tasks. The solution carried out by PT XYZ is to continue to provide a mindset for them to be a good employee and organize a more effective employee career planning schedule.